FAKTOR-FAKTOR YANG MEMPENGARUHI SERAPAN PENGAMBILAN KREDIT USAHA MIKRO KECIL DAN MENENGAH DI BANK RAKYAT INDONESIA UNIT SENTALO KABUPATEN KULON PROGO YOGYAKARTA - Netti Rinkei (Jurnal Dinamika Sosial Ekonomi, 2010)
This research purpose to analyze the influence of the length of business, the business of turnover, the total number of the employers, and the entrepreneurs education level and to know the level of labor absorption in agricultural, service, and trading sectors by small enterpreises that takes credit at BRI Unit Sentalo. The location of the research is at BRI Unit Sentalo on the credit units and object of the research is the entrerpreneur of small enterprises at BRI Unit Sentalo, Kulon Progo Regency Yogyakarta. The method of collecting data in the research uses census method. The reasearch used primary data and secondary data.  To determine the factors that influence the credit absorbtion of small enterprises using multiple linear regression analysis. The results of this research show that the length of business, the business turnover and the enterpreneurs education level affect to the credit absorbtion at BRI Unit Sentalo. Small enterprises that takes the credit at BRI Unit Sentalo can labors in agricultural, service and trading sector about 47,27%, I2, 50% and 28,95% respectively.Key Word: credit, small enterprises, labor absorbtion